Integrating Sipakatau and Sipakalebbi Values into Deep Learning Approaches for Character Education in Elementary Schools - Salmia; Dideng Kadir; Muh. Alka (Journal of Local Wisdom in Education, 2025)
Character education in primary schools demands pedagogical approaches that are culturally relevant and holistically oriented to foster ethical and moral development from an early age. The values of Sipakatau and Sipakalebbi, rooted in the Bugis-Makassar tradition, provide a strong foundation for social ethics and are highly applicable in shaping student behavior in educational contexts. This study examines the integration of these local wisdom values within a deep learning framework to enhance character education in elementary schools. Employing a qualitative systematic literature review, the research synthesizes findings from 45 peer-reviewed articles, proceedings, and scholarly texts published between 2015 and 2025, focusing on themes related to character education, contextual pedagogy, and ethnopedagogy. The results demonstrate that incorporating Sipakatau and Sipakalebbi through reflective, experiential, and culturally contextualized learning, such as folklore, role-playing, and community-based projects, encourages the internalization of moral values and promotes student engagement. The novelty of this study lies in its development of a culturally responsive conceptual model that links indigenous ethics with deep learning principles. The findings also emphasize the role of teachers as ethical facilitators and highlight the need for adaptive teaching modules tailored to students' sociocultural environments. Conclusively, this research contributes to the field of education by offering a transformative approach to character education that integrates local wisdom and by advancing the practical application of ethnopedagogical values in Indonesian elementary school curricula.